PERBEDAAN MODEL CONTEXTUAL TEACHING AND LEARNING BERPARADIGMA HUMANISTIK DAN MODEL CONTECTUAL TEACHING AND LEARNING BERPARADIGMA KEARIFAN LOKAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS VIII SMP MARIA GORETTI KABANJAHE T.P.2019/2020 (LPPM Universitas HKBP Nommensen, 2024)
This research is an experimental research with the type of research used is quasi-experimental research (pseudo-experiment) which aims to determine whether there are differences in the mathematical problem solving ability of students taught with the contextual teaching and lerning model with a humanistic paradigm with the contextual teaching and learning model with a local wisdom paradigm. The population in this study is the VIII grade of Maria Goretti Kabanjahe Junior High School T.P 2019/2020. After testing the posttest data on students' problem solving ability statistically, it was found that -count < table or tc> table with dk = 40 and dk = 60, namely (-0.997) < table (1.671) so that Ho was rejected and ha was accepted. So it can be concluded that the mathematical problem solving ability of students taught with Contextual Teaching and Learning with Local wisdom paradigm is higher than the mathematical problem solving ability of students taught using Contextual Teaching and Learning with Humanistic Paradigm on the topic of two variable linear equation system. Keywords: Creative Problem Solving, Concept Understanding